A FACS Based Case Study on Two HbE-β Thalassaemia Members of a Family, Having Similar Mutational Background. (18th April 2016) - Chatterjee, Tridip; Halder, Suchismita; Chakravarty, Amit; Chakravarty, Sudipa; Chakrabarti, Abhijit
Abstract : In this report we have tried to explain the reasons behind the difference in the pattern of transfusion requirement between two members of a family with similar β -globin mutation. The father and younger son both are HbE- β, but the father never had transfusion, whereas the younger son takes transfusion monthly. Mother and the elder son are HbEE without any history of transfusion. β -globin mutations of all family members were determined by ARMS-PCR. These were reconfirmed by direct sequencing of β -globin gene. Father and younger son were found to be Cod 26 (G-A)/IVS 1-5 (G-C), whereas mother and elder son were found to be Cod 26 (G-A)/Cod 26 (G-A). XmnI sequencing also revealed that all members of the family were CC. Then, flow cytometry study of red blood cells (RBCs) was performed to measure the oxidative stress of the RBCs. This study was also done on the light and dense fractions of the RBC population of the father and younger son. It was seen that the younger son suffers severe oxidative stress, which can be explained by his higher transfusion requirement. From our work, we have established the importance of taking oxidative stress of RBCs into consideration to explain the clinical manifestation and progression of haemoglobin related diseases like thalassaemia.